A Contrastive Analysis Of Interrogative Sentences In English and Indonesian - Ruth Monika Simanjuntak; Nadya Bersista E Marbun; Mutiara Rajagukguk; Anita Sitanggang (CV Putra Publisher, 2023)
The purpose of this article was to provide an overview of the survey Structures in Indonesian and English to explore similarities and Differences between them and make some predictions based on them These similarities and differences. This research uses descriptive qualitative research. In this study, data analysis was used according to Miles and Huberman using three methods for data analysis, namely data reduction, data visualization, and drawing conclusions. The purpose of this study is to find out